2017
DOI: 10.18805/lr-3564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spacing and fertilizer level on yield attributes of Dhaincha (Sesbania aculeata)

Abstract: A field experiment was conducted at Central Farm Unit situated in Agricultural College and Research Institute, Tamil Nadu Agricultural University, Killikulam during Rabi 2011-12 to evaluate the effect of spacing (120×30cm, 120×20 cm, 90×30 cm and 90×20 cm) and fertilizer levels (12.5:25:12.5, 18.75:37.5:18.75, 25:50:25, 31.25:62.5:31.25

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, no-till soybean yield responses to K fertilization were rarely significant with optimum to high K content soils (Borges and Mallarino, 2000). The enhancement of yield characters and yield might be due to the influence of adequate nutrients, helped the crop to perform better with growth and ultimately the yield (Rajesh et al, 2017) and split application of nitrogen is a better option to harness high seed productivity and to maintain soil fertility (Sharma et al, 2017).…”
Section: Effects Of Tillage Practices and Additional Fertilizer On Thmentioning
confidence: 99%
“…However, no-till soybean yield responses to K fertilization were rarely significant with optimum to high K content soils (Borges and Mallarino, 2000). The enhancement of yield characters and yield might be due to the influence of adequate nutrients, helped the crop to perform better with growth and ultimately the yield (Rajesh et al, 2017) and split application of nitrogen is a better option to harness high seed productivity and to maintain soil fertility (Sharma et al, 2017).…”
Section: Effects Of Tillage Practices and Additional Fertilizer On Thmentioning
confidence: 99%
“…As there is an emerging demand for dhaincha seeds, efficient agronomical interventions are required to ensure the seed quality and storage. Few researchers have attempted to study the effect of spacing, fertilizer level and different nutrient management practices on seed yield of dhaincha (Rajesh et al, 2017 andGopal et al, 2016). But Among the different seed production practices, harvesting and threshing are very much important operations as it has many impacts on post-harvest seed quality and viability.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that individual plant performances especially morphological growth characters reduce when there is an increase in plant density (Galanopoulou-Sendouka et al 1980) while wider spacing will cause more sunlight to be intercepted for photosynthesis, which leads to the production of more nutrients for partitioning for the development of more branches (Mehmet, 2008). Maximum light interception is possible when optimum plant space is provided right from early growth stage of the plant (Rajesh, et al, 2017). Total biomass production of a crop, with assumption of no water limitations, is the product of solar radiation received by the canopy of crop over the duration of the cropping period and the rate of efficiency by which the crop converts energy from light into plant dry matter (Richards, 2000).…”
Section: Introductionmentioning
confidence: 99%